2012
DOI: 10.3390/agronomy2040240
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Food Production in Africa by Boosting the Productivity of Understudied Crops

Abstract: Abstract:The Green Revolution has enabled Asian countries to boost their crop production enormously. However, Africa has not benefitted from this agricultural revolution since it did not consider local, but important crops grown in the continent. In addition to their versatile adaptation to extreme environmental conditions, African indigenous crops provide income for subsistence farmers and serve as staple food for the vast majority of low-income consumers. These crops, which are composed of cereals, legumes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 162 publications
(123 reference statements)
1
51
0
Order By: Relevance
“…Studies on the yield potential and gap for several of these crops including cassava and tef showed that crop productivity could be increased several-folds by using improved genotypes and/or management (for review, [8]). Since some studies showed that agricultural production can be improved in Africa through optimum use of inputs such as fertilizers, herbicides and pesticides [66,67], this sector needs to be given priority.…”
Section: Yield Potential Of Crops Cultivated In Africamentioning
confidence: 99%
“…Studies on the yield potential and gap for several of these crops including cassava and tef showed that crop productivity could be increased several-folds by using improved genotypes and/or management (for review, [8]). Since some studies showed that agricultural production can be improved in Africa through optimum use of inputs such as fertilizers, herbicides and pesticides [66,67], this sector needs to be given priority.…”
Section: Yield Potential Of Crops Cultivated In Africamentioning
confidence: 99%
“…One such example is illustrated by the Teff Research Project at the University of Bern in Switzerland, which has identified several semi‐dwarf and lodging‐tolerant teff lines in an EMS‐mutagenised population of more than 5000 lines (Tadele et al , ). These promising lines were then introgressed into high‐yielding teff cultivars, and the advanced breeding lines were evaluated in the field in Ethiopia (Tadele & Assefa, ). The first semi‐dwarf lodging‐tolerant teff mutant line, named kegne, was successfully developed from this mutagenised population (Jöst et al , ).…”
Section: The Good the Bad And The Future Of Teffmentioning
confidence: 99%
“…When this occurs, both the yield and the quality of the grain and the straw are severely reduced and both manual and mechanical harvesting are impeded. Various attempts have been made by the research community to develop lodging-resistant tef cultivars (Assefa et al, 2011; Tadele and Assefa, 2012) but presently no cultivar with reasonable lodging resistance has been obtained.…”
Section: Introductionmentioning
confidence: 99%